2005
DOI: 10.1038/nature03674
|View full text |Cite
|
Sign up to set email alerts
|

Geomagnetic dipole strength and reversal rate over the past two million years

Abstract: Independent records of relative magnetic palaeointensity from sediment cores in different areas of the world can be stacked together to extract the evolution of the geomagnetic dipole moment and thus provide information regarding the processes governing the geodynamo. So far, this procedure has been limited to the past 800,000 years (800 kyr; ref. 3), which does not include any geomagnetic reversals. Here we present a composite curve that shows the evolution of the dipole moment during the past two million yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
393
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 420 publications
(418 citation statements)
references
References 29 publications
23
393
2
Order By: Relevance
“…This behavior contrast with the long-term "memory" of the dipole field considered by Cande [41] to account for the anomalous skewness of marine magnetic anomalies, and by Valet and Meynadier [8] to account for the "sawtooth pattern" observed in the paleointensity fluctuations over the past 4 Myr. But it is not in contradiction with the recent update by Valet et al [9], which now argues in favour of a slow decrease in paleointensity only during a period of about 60-80 kyr before reversals.…”
Section: Discussioncontrasting
confidence: 47%
See 2 more Smart Citations
“…This behavior contrast with the long-term "memory" of the dipole field considered by Cande [41] to account for the anomalous skewness of marine magnetic anomalies, and by Valet and Meynadier [8] to account for the "sawtooth pattern" observed in the paleointensity fluctuations over the past 4 Myr. But it is not in contradiction with the recent update by Valet et al [9], which now argues in favour of a slow decrease in paleointensity only during a period of about 60-80 kyr before reversals.…”
Section: Discussioncontrasting
confidence: 47%
“…Useful insight on the origin of tiny wiggles can however be gained from the few available highresolution magnetostratigraphic paleointensity studies covering the past few Myr (see for instance, [25] for the Brunhes period; [26] for the Matuyama period; [27] for the Matuyama and late Gauss periods; [9] for the past 2 Myr; [8] for the past 4 Myr; [28] for chrons 5n; [29] for chrons 6Bn to 13n; [30] for chrons 12r to 13r). These studies have shown that the magnetic polarity time scale mainly determined from marine magnetic anomalies is almost complete and that only a few tiny wiggles detected so far can be ascribed to additional short polarity intervals (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We observe that the regimes with given polarity involve an amplitude of the azimuthal field in the range 50-100 G. The amplitude very slowly decays before each reversal and displays a strong overshoot immediately after. Similar features have been reported in some palaeomagnetic recordings of the Earth's magnetic field [10]. Another open question in palaeomagnetism concerns the variation of the mean frequency of reversals over the geological ages.…”
Section: Prl 101 074502 (2008) P H Y S I C a L R E V I E W L E T T Esupporting
confidence: 54%
“…Jicha et al, 2011). The entire period between~120 ka and~100 ka is characterized by a low intensity of the Earth's magnetic field (Valet et al, 2005) which would make the chance that excursions or even reversals of the field occur higher than for other periods. However, changes in palaeomagnetic directions during 100e120 ka are described only at the older age range (Blake Event) and, occasionally, at the younger age range (post-Blake).…”
Section: Discussionmentioning
confidence: 99%